Development of nano-emulsions based on Ayapana triplinervis essential oil for the control of Aedes aegypti larvae. - Alex Bruno Lobato Rodrigues; Rosany Lopes Martins; Érica de Menezes Rabelo; Rosana Tomazi; Lizandra Lima Santos; Lethícia Barreto Brandão; Cleidjane Gomes Faustino; Ana Luzia Ferreira Farias; Cleydson Breno Rodrigues Dos Santos; Patrick de Castro Cantuária; Allan Kardec Ribeiro Galardo; Sheylla Susan Moreira da Silva de Almeida (PLoS ONE)
Ayapana triplinervis is a plant species used in traditional medicine and in mystical-religious rituals by traditional communities in the Amazon. The aim of this study are to develop a nano-emulsion containing essential oil from A. triplinervis morphotypes, to evaluate larvicidal activity against Aedes aegypti and acute oral toxicity in Swiss albino mice (Mus musculus). The essential oils were extracted by steam dragging, identified by gas chromatography coupled to mass spectrometry, and nano-emulsions were prepared using the low energy method. Phytochemical analyses indicated the major compounds, expressed as area percentage, β-Caryophyllene (45.93%) and Thymohydroquinone Dimethyl Ether (32.93%) in morphotype A; and Thymohydroquinone Dimethyl Ether (84.53%) was found in morphotype B. Morphotype A essential oil nano-emulsion showed a particle size of 101.400 ± 0.971 nm (polydispersity index = 0.124 ± 0.009 and zeta potential = -19.300 ± 0.787 mV). Morphotype B essential oil nano-emulsion had a particle size of 104.567 ± 0.416 nm (polydispersity index = 0.168 ± 0.016 and zeta potential = -27.700 ± 1.307 mV). Histomorphological analyses showed the presence of inflammatory cells in the liver of animals treated with morphotype A essential oil nano-emulsion (MAEON) and morphotype B essential oil nano-emulsion (MBEON). Congestion and the presence of transudate with leukocyte infiltration in the lung of animals treated with MAEON were observed. The nano-emulsions containing essential oils of A. triplinervis morphotypes showed an effective nanobiotechnological product in the chemical control of A. aegypti larvae with minimal toxicological action for non-target mammals.